Risk Factors for Cervical Cancer and Papanicolaou Test in Marginalized Adolescents in Bogotá, Colombia (2020)
Introduction: Cervical cancer is rare in young women, so screening in women under 21 years is not recommended. However, early and intense exposure to risk factors could increase the likelihood of early pre-neoplastic lesions. Currently, particular social conditions in adolescents can favor exposure, generate changes in lifestyles, and affect their immediate and future health. This work describes the frequency of risk factors and Pap results in adolescents of a child protection center. Materials and Methods: This paper presents a retrospective cross-sectional study that measured the frequency of exposure to risk factors for cervical cancer and Pap results of 889 adolescents exposed to critical social conditions. It used information from the cytology report files made between 2011 and 2016. Results: Normal Pap smear was found in 85 % of the cases. The risk factors had a very high prevalence, especially the early age of onset of sexual relations with 75 % before age 14, the number of sexual partners with more than one in 66.7 %, no use of a condom 95 % and high cigarette consumption. Discussion: The frequency of pre-malignant cervical lesions was very low; however, in women under 21 years old with premature and intense exposure to risk factors, an early-onset conservative screening accompanied by gynecological consultation for prevention, diagnosis, or treatment can be considered. The marginalized adolescent's social problem requires interdisciplinary and intersectoral management.